The Dynamics of Federalism in National and Supranational Political Systems - Pagano, Michael A. author. aut Link
XVIII, 346 p.
Keywords: This collection of essays is designed to help scholars and practitioners understand the fluid and dynamic nature of federalism, with particular emphasis on the federal system in the United States. The book is written to aid our understanding of the contemporary question 'which federalism?'.